Officer Accommodation in Police-Civilian Encounters: Reported Compliance with Police in Mongolia and the United States - Barker, Valerie; Choi, Charles; Giles, Howard; Hajek, Christopher (Mongolian Journal of International Affairs, 2011)
Recent research has demonstrated that, for young adults, officers' communicative practices are potent predictors of civilians’ attributed trust in police, and their perceived likelihood of compliance with police requests. This line of work has important applied implications for ameliorating police-civilian relations on the one hand and promoting a joint law enforcement/community response to crime prevention on the other. The present study continued this line of work in Mongolia and the USA. Mongolia is not only intriguing as little communication research has been conducted in this setting, but is significant as its government (and the law enforcement arm of it) is currently experiencing significant social upheavals. Besides differences between nations, results revealed that, for American participants, officer accommodativeness indirectly predicted civilian compliance through trust. This also emerged for the Mongolian counterparts, although a direct relationship was evident between officer accommodation and compliance as well. The latter finding is unique in that it is the first cultural context where both direct and indirect paths have been identified. The practical significance of these findings is discussed. Keywords: Mongolia; United States; America; Police; Law Enforcement; Civilian; Intercultural; Cross-Cultural; Intergroup; Accommodation; Trust; Compliance. DOI: 10.5564/mjia.v0i15-16.35 Mongolian Journal of International Affairs No.15-16 2008-2009 pp.176-200